Comparative analysis of Dipyrone in tablet and capsule forms: Industrial versus compounded pharmaceutical preparations (Research, Society and Development, 2025)
Dipyrone (metamizole) is a widely used drug due to its analgesic, antipyretic, and spasmolytic properties. Despite its effectiveness and low cost, its safety remains under debate, especially due to its association with rare cases of agranulocytosis. In Brazil, it remains an essential medicine, available in various formulations, both industrially produced and compounded. With the growth of the compounding sector and the demand for personalized formulations, concerns arise regarding the quality and efficacy of these products compared to industrial versions. This study aimed to evaluate and compare the quality of dipyrone capsules and tablets from industrial and compounding pharmacies in the city of Pindamonhangaba - SP. Physicochemical tests of identification, assay, and disintegration were performed, following methodologies established in the 6th edition of the Brazilian Pharmacopoeia. The analyses verified the presence of the active ingredient, dosage compliance, and disintegration time of the samples. The results contribute to ensuring the quality of medications and patient safety, highlighting the importance of rigorous quality control in both industrial manufacturing and pharmaceutical compounding.